Multiple sources for Archean granitoids in the Yalgoo area, Yilgarn Craton, Western Australia: Geochemical and isotopic evidence - Ameen, S.M.Mahbubul; Wilde, Simon (Elsevier BV, 2018)
© 2018 Elsevier B.V. In the Yalgoo area of the north-central Yilgarn Craton, three small granitoid bodies, named the Lady Lydia (LLG), Yalgoo east (YEG) and Yalgoo north granitoids (YNG) intruded ~2.8 Ga mafic supracrustal rocks. They form two suites: i) granodiorites (from both the LLG and YEG) with strongly fractionated REE patterns, high LREE contents, low HREE contents, weakly positive Eu anomalies, and of Archean TTG affinity, and ii) biotite monzogranites (from the YNG) with very high LREE contents and prominent negative Eu anomalies. All the granitoids are calc-alkaline, with the granodiorites recording ages of 2763–2752 Ma, and the biotite monzogranites recording ages of 2636–2634 Ma. The REE and HFSE characteristics of the granodiorites favor an Archean subduction environment. Abundant xenocrystic zircons (3.00–2.94 Ga) in the granodiorites and their Lu-Hf isotopic characteristics imply a long history of crustal recycling in the north-central Yilgarn. The Lu-Hf isotopes indicate that the ~2.76 Ga granodiorites and xenocrysts were formed from a composite source ranging in age from 3.5 to 3.0 Ga. Increased crustal thickening due to convergence (after cessation of subduction) caused melting in the upper/mid-crustal levels, with generation of parental melt at ~2.64 Ga to source the biotite monzogranites. The latter are characterized by strongly -ve eHf(t) (-10 to -12) and largely Eoarchean TDM2(Hf) model ages (~3.85–3.6 Ga). Significantly, they provide evidence of Eoarchean crustal material in this part of the Yilgarn Craton.